Health-related quality of life and associated factors among Onchocerciasis patients in southeast Nigeria: A cross-sectional comparative study - Adah E. Otache; Ifeyinwa L. Ezenwosu; Edmund N. Ossai; Elias C. Aniwada; Emmanuel A. Nwobi; Benjamin SC. Uzochukwu (Public Library of Science (PLoS), 2022)
Introduction Onchocerciasis, a neglected tropical disease of public health importance, causes chronic morbidity and severe disability that may impact on health-related quality of life (HRQoL) of the infected people. This study assessed the HRQoL and associated factors among onchocerciasis patients in southeast Nigeria. Methods This was a community-based cross-sectional comparative study. Using a multistage sampling technique, 340 onchocerciasis patients were selected and matched for age and gender with the healthy population in the same neighbourhood. The respondents were interviewed using the short-form-36 (SF-36) questionnaire to determine their HRQoL. WHO Disability Assessment Schedule 2.0 tool (WHODAS 2.0) was used to assess disability in persons with onchocerciasis. Means were compared with independent student t-test while Chi-square test was used to compare proportions. Also, correlation analysis and logistic regression were used in the analyses. Results A significantly lower proportion of people living with onchocerciasis had a good quality of life when compared with the healthy subjects (69.4% vs 93.5%, p<0.001). Also, an inverse relationship was seen between disability and quality of life in the onchocerciasis group (r = -0.647, p<0.001). Predictors of poor quality of life among respondents with onchocerciasis were: respondents aged ≥48 years (AOR = 2.5, 95% CI: 1.4-5.0), those with some disability associated with onchocerciasis (AOR = 3.33, 95%CI: 1.4-5.0) and respondents who perceived themselves as a burden to people (AOR = 10, 95%CI: 2.5-20). Conclusion Onchocerciasis impacted negatively on HRQoL of persons with onchocerciasis when compared with the healthy population. The quality of life of persons affected with onchocerciasis reduces with increasing disability. There is the need to increase community awareness on onchocerciasis to ensure early diagnosis and prompt treatment as this will reduce disability among those affected with the disease thus enhancing their HRQoL. Author summary Onchocerciasis is a neglected tropical disease caused by Onchocerca volvulus, a filarial nematode that is transmitted through the bite of infected blackflies of the genus Simulium. The disease manifests either as ocular or as dermal onchocerciasis with several symptoms including itching, nodules, skin thickening, visual impairment and blindness. The disease is still of public health concern especially in the study area where it is endemic and causes debilitating symptoms. This study assessed the Health-related quality of life and associated factors among persons with onchocerciasis. The findings of this study showed that the quality of life of onchocerciasis patients was lower than the healthy population. Also, an increased level of disability among the onchocerciasis patients leads to a reduction in their quality of life which worsens with increasing age. Health professionals should be aware of these findings because it will help them implement and continue community awareness programs on onchocerciasis for early detection and treatment to reduce disability and enhance health-related quality of life.